Dispositivos de Alivio a Presión Conforme a la Sección VIII, Div.1 del Código ASME - Rivera Mendoza, Orlando R. (My University, 2005)
Objetivo General: Proporcionar los conocimientos mínimos requeridos para la selección, certificación e instalación de válvulas de seguridad y discos de ruptura para cualquier recipiente sujeto a presión conforme a los requisitos obligatorios establecidos en la Sección VII, División 1 del Código ASME.
Keywords: Dispositivos de alivio a presión; Pressure relief devices, pressure relief valves, marking, certification of capacity of pressure relief devices, determination of pressure relieving requirements, pressure setting of pressure relief devices, installation, minimum requirements for pressure relief values, minimum requirements for rupture disk devices, capacity conversions for safety valves, determination of certified relieving capacities, heating boilers, pressure vessels